The Impact of Traffic Congestion on the Mental Health of Civil Servants: A Case Study of Ministry of Transportation Employees in the Greater Jakarta Area - Fitria Brilianti, Dani; Rokhim, Abdul; Basuki, Ahmad (Advances In Social Humanities Research, 2024)
This study aims to investigate the psychological effects of prolonged traffic congestion on civil servants working in the Ministry of Transportation in the Greater Jakarta Area. As one of the most densely populated regions in Indonesia, Greater Jakarta experiences severe daily traffic, which has the potential to exacerbate mental health issues. The research employed a quantitative approach through a structured survey distributed to 102 respondents. The respondents were classified into three categories of mental health disorders: high, moderate, and low, based on validated psychological scales. The results indicated that 51.20% of respondents experienced severe mental health disorders, while 39.21% reported moderate disorders, and 8.82% exhibited mild symptoms. Emotional regulation difficulties, anxiety, and mood disturbances were significantly related to traffic exposure. The study recommends implementing flexible work arrangements, improving public transportation infrastructure, and providing mental health support programs to mitigate the adverse effects of traffic congestion on civil servants. These findings highlight the need for urgent policy interventions to promote the well-being of public servants in urban settings, particularly those affected by chronic congestion.